Local Politics and Contemporary Transformations in the Arab World
XV, 242 p.
Keywords: The contributors link innovative analytical concepts and ethnographic in-depth case studies from the Arab world. Based on the debates on politics from below and dynamic concepts of state, all the chapters focus on informal institutions, non-elite actors, and the dynamic and contradictory relationship between state and society.